The relationship between learning independence, motivation, science literacy skills, and learning outcomes of public high school students in North Kolaka Regency - Daud, Firdaus; Mu'nisa, Andi; Marwidayanti, Marwidayanti (Jurnal Mangifera Edu, 2025)
The purpose of this study was to determine the relationship between learning independence, learning motivation, science literacy skills, and the learning outcomes of students in grade XI at Public High School in North Kolaka Regency. This type of research is quantitative, employing an ex-post facto correlational approach. Data acquisition using non-test instruments, such as questionnaires, to assess learning independence and motivation. Administer test instruments, including essays and multiple-choice questions, on digestive system material to assess science literacy skills and learning outcomes. Descriptive statistical data analysis, and inferential statistical data analysis in the form of prerequisite tests (normality test, linearity test, heteroscedasticity test, and Multicolinerity test), hypothesis testing (simple linear regression analysis and multiple linear regression analysis). The value of the correlation coefficient (R) for students is 0.848, with an R-squared value or coefficient of determination of 0.719, and a significant level of 0.000. There is a positive and significant relationship between learning independence, learning motivation, and science literacy with students' learning outcomes on digestive system material at North Kolaka Regency SMAN. These three factors together contribute 71.9% to learning outcomes. Based on the correlation coefficient value, it is known that the relationship between learning independence, motivation, and science literacy skills is in the "strong" category based on the correlation coefficient guideline, the value of R Variable learning independence, learning motivation, science literacy skills predict learning outcomes on the digestive system material is significant between learning independence, learning motivation, science literacy skills with student learning outcomes.